2024
DOI: 10.1002/cam4.6903
|View full text |Cite
|
Sign up to set email alerts
|

The influence of “bad news” and “neutral/good news” on patients' perception of physician empathy during oncology consultations

Mattias Tranberg,
Henrik Ekedahl,
Carl Johan Fürst
et al.

Abstract: ObjectivesBeing met with empathy increases information sharing, treatment coherence, and helps patients to recover faster. However, we do not know how the content of the conversation about disease progression, new treatments, or other issues concerning serious illness affects patients' perceptions of the physician's empathy, and thus, the quality of the conversation. This study aimed to test the hypothesis that patients will rate their physician lower following a “bad news” consultation using the consultation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 31 publications
0
1
0
Order By: Relevance
“…Findings from multiple studies in various settings show that recipients tend to blame the messengers, find them less empathic (Tranberg et al, 2024), and ascribe to them malign intent even when the status quo is out of the messengers' control (John et al, 2019). Even though physicians are expected to encourage and allow their recipients to express themselves within reasonable limits (Lee et al, 2002), physicians themselves become vulnerable in these situations, and several studies have shown that they therefore suffer physiological stress reactions (Studer et al, 2017), along with feelings of anxiety, guilt, exhaustion, failure, and frustration (Bousquet et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Findings from multiple studies in various settings show that recipients tend to blame the messengers, find them less empathic (Tranberg et al, 2024), and ascribe to them malign intent even when the status quo is out of the messengers' control (John et al, 2019). Even though physicians are expected to encourage and allow their recipients to express themselves within reasonable limits (Lee et al, 2002), physicians themselves become vulnerable in these situations, and several studies have shown that they therefore suffer physiological stress reactions (Studer et al, 2017), along with feelings of anxiety, guilt, exhaustion, failure, and frustration (Bousquet et al, 2015).…”
Section: Introductionmentioning
confidence: 99%